Transmission of exchange rate variation for the brazilian export prices of rice: a comparative study of dollar and baht (Research, Society and Development, 2020)
The objective of this work consisted on the relation exam between exchange rates and the Brazilian export prices of rice, relation defined as the pass-through of the exchange rate, having as reference the period from January, 1997 to February, 2019. For this, we estimated two models: in dollar and in baht (Thai currency). Data was collected in the sites of Ministry of Development, Industry and Foreign Trade – MDIC, Institute for Applied Economics – IPEA, Central Bank of Brazil – BCB and WORLD BANK. In this sense, we used the instrumentals of time series, especially of the Vector Error Correction Model. The results found provided indications that the pass-through degree of the exchange rate for the export prices of rice occurred in an incomplete way for dollar indicating that the depreciations of exchange rates in dollar do not translate themselves in significant gains of competitiveness, since that they do not reduce expressively the export prices. Yet, for the estimated model in baht, the pass-through was completed, indicating that the exchange variations are fully passed on to the export price in baht, indicating competitiveness.